Adverse fetal/neonatal and obstetric outcomes in pregnant women with heart disease: Data from the Registry of Pregnancy and Cardiac Disease (ROPAC) of the Kermanshah, Iran - Nasrin Mansouri; Ali Azizi; Maryam Sayyadi; Marzieh Bagherinia (PLoS ONE, 2026)
Background Pregnancy complicated by heart disease can pose serious risks and complications for both the mother and the fetus. Understanding the prevalence of these conditions during pregnancy, along with the various types of cardiac diseases and their associated complications, is essential for reducing maternal and fetal morbidity and mortality during pregnancy and childbirth. Objective This study aims to examine the clinical characteristics, risk factors, and outcomes of heart disease in pregnant women. Methods This single-center prospective registry-based cohort study without a comparison group (single arm) was conducted using data from the Cardiac Disease Registry for pregnant women in Kermanshah, Iran. All pregnant women with structural heart diseases-including congenital heart disease, valvular disease, prosthetic heart valves, cardiomyopathy, ischemic heart disease, aortopathy, and arrhythmias-were included. Data were collected using validated checklists and entered into an online registry. Results A total of 36 pregnant women with heart disease were included. The most common diagnoses were congenital heart disease (38.9%), valvular heart disease (30.6%), and cardiomyopathy (22.2%). Most patients (94.5%) had preserved left ventricular ejection fraction (LVEF ≥40%), and 88.9% had pre-existing cardiac disease, with 86.2% receiving pre-pregnancy cardiac counseling. No cases of maternal or neonatal mortality were observed. New-onset heart failure occurred in 13.9% of women, and 27.8% required hospitalization for cardiac reasons during pregnancy. The total abortion rate was 19.4% (11.1% spontaneous, 8.3% therapeutic). Preterm birth occurred in 24.1% of cases, and low birth weight in 17.2%. The cesarean delivery rate was high (80.6%). Hypertensive disorders and gestational diabetes were relatively uncommon. No congenital heart defects were observed in neonates. Conclusion Comprehensive pre-pregnancy counseling, specialized prenatal care, and multidisciplinary management can lead to favorable maternal and neonatal outcomes in high-risk pregnancies complicated by heart disease. The absence of mortality in this cohort highlights the effectiveness of organized care models. Despite the limited sample size, these findings underscore the value of structured, registry-based approaches to improving outcomes in pregnant women with cardiac disease.